2015
DOI: 10.1007/s12011-015-0573-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Liver Antioxidant Status of Offspring Mice Induced by Maternal Fluoride Exposure During Gestation and Lactation

Abstract: Excessive fluoride intake for a long time has been demonstrated to provoke hepatic oxidative stress in adults. However, the response to fluoride toxicity of liver in newborns exposed to fluoride during embryonic and suckling stages remains unclear. In this study, female Kunming mice were administrated with 25, 50, and 100 mg/L sodium fluoride (NaF) from prenatal day 0 to day 21 after delivery, and the antioxidative status in the liver of their pups at postnatal day 21 was evaluated. The results showed that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Several studies report reduced enzymatic activity after fluoride exposure, followed by oxidative damage [ 48 50 ]. Other studies show that fluoride reduces CAT activity and GSH levels, but not the activity of SOD activity in human erythrocytes [ 49 ] and in the liver of mice [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report reduced enzymatic activity after fluoride exposure, followed by oxidative damage [ 48 50 ]. Other studies show that fluoride reduces CAT activity and GSH levels, but not the activity of SOD activity in human erythrocytes [ 49 ] and in the liver of mice [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous examples of F toxicity in living organisms, such as in humans, guinea pigs, roe deers, donkeys, quails, rats, and even carps . A lot of studies have shown that excessive exposure to F may result in detrimental effects on many organs and tissues, such as the brain, liver, kidney, testicle, and so on. However, lesions of skeleton and teeth by F are still the main problems of fluorosis …”
Section: Introductionmentioning
confidence: 99%
“…The amount of F in an organism is extremely small, and about 90% of it is distributed in skeletons and teeth. 1 At high concentrations, F can cause damage to multiple organs and tissues, such as in the brain, [2][3][4] reproduction organs, [5][6][7] liver, 8,9 spleen, 10 thyroid, [11][12][13] and especially to the skeleton and teeth, which can progress to fluorosis. [14][15][16] Dental fluorosis is a well-known chronic metabolic disease caused by the prolonged presence of ingested excessive amounts of fluoride, [17][18][19] characterized by tooth discoloration.…”
Section: Introductionmentioning
confidence: 99%